KEMAMPUAN MENULIS KARANGAN NARASI EKSPOSITORIS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPEATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) SISWA KELAS VII SMP NEGERI 2 BAYANG - Wulandari, Indah; Mana, Lira Hayu Afdetis; Andheska, Harry (Pendidikan Bahasa Indonesia, 2013)
This research is motivated by the students interest in narrative writing skills are still low. Problems encountered is the difficulty students in expressing ideas or his mind in the form of expository writing, students difficulty in determining the characteristics of narrative essays, students difficulties in distinguishing narrative essay examples. This is due to the teachers not on the use of learning methods. This study aimed to describe the narrative expository essay writing skills using cooperative learning model CIRC class VII SMP Negeri 2 Bayang.This type of research is a quantitative study using descriptive methods. The study population was a class VII student of SMP Negeri 2 Imagine the academic year 2012/2013. Number of students, the population in this study were 210 students, which is scattered in seven classes. The sample was 32 people (15% x number of population per class). The data obtained in this study by giving a test to the students.             The results can be seen the following things. First, the ability of students to write an expository essay narrative using cooperative learning model (CIRC) class VII student of SMP Negeri 2 Bayang for Indicator 1 (written language to expand knowledge) are at sufficient qualifications (C) with an average of 63.75 students abilities. Second, Indicator 2 (conveying information about an event in chronological order) is more than enough in qualifying (LDC) with an average of 66.88 students abilities. Third, Indicator 3 (the language used is more likely to kebahasa informative with emphasis on the use of denotative words) are on qualified enough (C) with an average of 56.25 students abilities. Based on the research that has been conducted on the ability of narrative expository essay writing using cooperative learning model (CIRC) class VII student of SMP Negeri 2 Bayang, it can be concluded that the ability to write narrative expository essay using cooperative learning model (CIRC), a student of class VII SMP Negeri 2 Imagine obtaining an average of 63.81 , is in the range 56-65 % qualified enough (C). The study is expected to be Indonesian teacher at SMP Negeri 2 shadow to enhance students understanding back narrative expository essay